The Study on the Sustainable Patterns of Grassroots Innovations in the Clusters of Micro-Enterprises - Lin, Yao-Chin; Chen, Chun-Liang; Chen, Wei-Hung (European Journal of Sustainable Development, 2018)
The purpose of this study is to find out different patterns of grassroots innovation under the circumstances of clustering and sustainable development of Micro-enterprises (MIEs). The research object is the clustering of MIEs in Taiwan. This study collects data through interviews, secondary data, observation and expert meeting etc. This study found four patterns promote the sustainable development of grassroots innovation. 1. Pattern I is ability high and trigger high, is defined as “Sustainable Development”. 2. Pattern II is ability high and trigger low, is defined as “Ability-oriented”. 3. Pattern III is ability low and trigger low, is defined as “Newborn”. 4. Pattern IV is ability low and trigger high, is defined as “Leader-oriented”. Moreover, the study identifies practical implications and proposes suggestions for future research. This study also provides clear guidance on government policies, clustering companies, counseling consultants, and the four patterns to promote sustainability. Keywords: Grassroots Innovations, Micro-Enterprises’ Cluster, Sustainability